1997
DOI: 10.1021/ic960639x
|View full text |Cite
|
Sign up to set email alerts
|

trans-Difluorosilicon(IV) Complexes of Tetra-p-tolylporphyrin and Tetrakis(p-(trifluoromethyl)phenyl)porphyrin:  Crystal Structures and Unprecedented Reactivity in Hexacoordinate Difluorosilanes1

Abstract: Single-crystal X-ray structures have been determined for the difluoro(porphyrinato)silicon(IV) complexes trans-(Por)SiF(2) (Por = the dianions of tetra-p-tolylporphyrin (TTP) and tetrakis(p-(trifluoromethyl)phenyl)porphyrin). Crystallographic data for (TTP)SiF(2).Et(2)O: monoclinic, space group C2/c, a = 30.228(4) Å, b = 9.913(4) Å, c = 15.474(5) Å, alpha = gamma = 90 degrees, beta = 114.58(3) degrees, V = 4217(2) Å(3), Z = 4, R1 = 0.0588. Crystallographic data for (TTFP)SiF(2): monoclinic, space group C2/c, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…Silicon(iv) porphyrin complexes readily conform to this trend. Single crystal X-ray diffraction studies on (TTP)SiF2 [47] and (TTP)Si(OTf)z [ 171 show that the fluoride derivative is less ruffled than the triflate derivative and our electrochemical studies ( Table 1) have shown that the fluoride derivative is easier to reduce.…”
Section: Planarity Of the Porphyrin Ringmentioning
confidence: 70%
“…Silicon(iv) porphyrin complexes readily conform to this trend. Single crystal X-ray diffraction studies on (TTP)SiF2 [47] and (TTP)Si(OTf)z [ 171 show that the fluoride derivative is less ruffled than the triflate derivative and our electrochemical studies ( Table 1) have shown that the fluoride derivative is easier to reduce.…”
Section: Planarity Of the Porphyrin Ringmentioning
confidence: 70%
“…(see the ruffling dihedrals  listed in Table 1). 26,27 A plausible explanation for this difference is that there is less of an energy cost associated with nonplanar deformation of an antiaromatic isophlorin relative to an aromatic porphyrin. 28,29,30 Peripheral bond length alternation and ruffling together result in an overall lower molecular symmetry, D2, for the reduced six-coordinate complexes E(TPP)L2, which may be compared with D2d for Si(TPP)F2…”
Section: Resultsmentioning
confidence: 99%
“…(RITFOP 26 ) and approximately D4h for Ge(TPP)Cl2 (NIPKEC 27 ). For the four-coordinate complex Ge(TPP), the calculations also led to a delocalized structure, consistent with an aromatic Ge II (Por 2-) formulation and in excellent agreement with the crystal structure (LIJVAC 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Formerly published hexacoordinate difluorosilicon complexes with trans-situated fluorine atoms were equipped with rather rigide tetradentate chelating ligands, e.g. salen or porphyrine [5,8]. The conversion of 2c into the cis-configured complex in solution indicates to a small energy gap between both isomers.…”
Section: Methodsmentioning
confidence: 99%